NURTURING DIGITAL MEDIA PROFESSIONALS: INSIGHTS FROM UNIVERSITY-ENTERPRISE COLLABORATION - Chen, Wei (Top Educational Review Journal (TERJ), 2024)
Digital media technology education is a multifaceted field encompassing digital technology, media technology, and art design. It centers on fostering creativity, enabling students to employ digital media technology for research and innovation within related domains. The primary goal is to produce adept professionals capable of proficiently applying digital media technology in industries like media production and animation design. The incorporation of school-enterprise cooperation in digital media technology education serves a dual purpose. On one hand, it aligns more closely with market needs, allowing institutions to stay attuned to evolving market demands through feedback from collaborating enterprises. Schools can then tailor multimedia technology education to develop students’ skills and aptitudes, producing professionals better suited to meet market requirements. On the other hand, school-enterprise cooperation nurtures a mutually beneficial relationship between educational institutions and enterprises. This cooperative model combines schools’ theoretical expertise with enterprises’ practical training and market insights, resulting in complementary strengths and resource savings. The collaboration forms a win-win training approach for cultivating digital media technology talents